QUALIDADE DE VIDA DE PACIENTES ASSISTIDOS EM UM CENTRO DE ALTA COMPLEXIDADE EM ONCOLOGIA - Moraes, Fernanda D.; Berlezi, Evelise M.; Kolankiewicz, Adriane B.; Rosanelli, Cleci L. P.; Loro, Marli M.; Gomes, Joseila S.; Franco, Francieli P. (Salão do Conhecimento, 2013)
Resumo